Affective, cognitive, and behavioral outcomes from a resident personal finance curriculum pilot project. Issue 3 (30th June 2021) - Shappell, Eric; Ahn, James; Park, Yoon Soo; McKillip, Ryan; Ernst, Michael; Pirotte, Matthew; Tekian, Ara
Abstract: Background: The transition to residency marks a significant shift in the financial circumstances of medical trainees. Despite existing resources, residents still cite uncertainty in this domain. A personal finance curriculum is needed to close this educational gap and improve the financial well‐being of trainees. Methods: The curriculum was developed using Kern's framework. Two needs assessments informed the consensus development of goals and objectives, educational strategies, and assessments. Course material was hosted online for asynchronous review and complemented by two 1‐hour webinars. The curriculum was piloted at one institution. Participants completed (1) knowledge assessments before and after the intervention, (2) a survey of reactions to the curriculum, and (3) an assessment of financial behavioral changes after the intervention. Results: Thirty‐seven residents (37/49, 76%) enrolled in the curriculum. Among participants, 20 (20/37, 54%) completed the curriculum. Most participants agreed or strongly agreed that the content was relevant (20/20, 100%) and clearly presented (19/20, 95%) and that they would recommend the curriculum to other residents (20/20, 100%). Performance on the knowledge assessment improved 21% after the intervention (mean ± SD = pretest 57% ± 17%, posttest = 78% ± 12%; p < 0.001). Most residents (17/20, 85%) also reported behavioral changes including setting new financial goals (12/20, 60%), taking new action toward financial planning (11/20, 55%), and changing financial habits (6/20, 30%). There were no direct financial costs incurred in the implementation of this pilot. Conclusions: This is a successful pilot of a virtual personal finance curriculum with positive outcomes data. Addressing this problem at scale will require buy‐in from educators around the country to deliver this information to residents that may not otherwise seek it out. Future study should assess curricular outcomes in other settings and the durability of acquired knowledge and behavioral changes over time.